Real-world effectiveness of the CoronaVac vaccine in a retrospective population-based cohort in four Colombian cities (2021-2022) - Reina-Bolaños, Carlos Alberto; Arbeláez-Montoya, María Patricia; Brango, Hugo; Ortega, Delia; Tovar-Acero, Catalina; López-Carvajal, Liliana; Hincapié-Palacio, Doracelly; Agudelo-Vacca, Ana Maritza; Avila-Rodriguez, Germán; Avilés-Vergara, Paula A; Minotta-Díaz, Ingrid Liliana; Arango-Londoño, David; et al. (International journal of infectious diseases, 2024)
•CoronaVac reduces risk of COVID-19 death by 90%.•The highest vaccine effectiveness is observed in the first 4 months.•Booster doses do not boost the effectiveness CoronaVac.•The vaccine is less effective against infections (32%).•The vaccine provides high protection for subjects aged 3-12 and those over 60. The National Vaccination Plan against SARS-CoV-2/COVID-19 was launched by the Ministry of Health and Social Protection on 14 February 2021. The main objective of this study was to evaluate the effectiveness of the CoronaVac in preventing the three clinical outcomes of infection, hospitalisation, or death, in a real-world scenario. This was a population-based retrospective dynamic cohort study using a multivariate Cox model to calculate hazard ratios to estimate vaccine effectiveness from 17 February 2021 to 30 June 2022. The data were collected from surveillance systems for 12 months for each individual. Four cities were selected on the basis of the reliability of their data bases. The rates of CoronaVac effectiveness were 32% (95% confidence interval [CI] 31-33) for preventing infection, 55% (95% CI 54-56) for hospitalisation, and 90% (95% CI 89-90) for death, at the end of follow-up. These findings were more consistent during the first 4 months. Compared with the unvaccinated group, homologous booster doses appeared to increase effectiveness in preventing hospitalisation, whereas heterologous booster doses increased protection for both hospitalisation and death. Booster doses did not improve effectiveness among those already vaccinated with CoronaVac, even when they received heterologous boosters. CoronaVac demonstrated effectiveness in preventing death and hospitalisation during the first year of follow-up, but its effectiveness in preventing infection was lower, decreasing rapidly after the first 4 months of follow-up. The effectiveness was higher among children aged between 3 and 12 years, and among adults aged ≥60 years. Booster doses did not improve effectiveness among those already vaccinated with CoronaVac.